1769d Combination of mirnas, mesothelin and fibulin-3 as potential biomarkers in malignant pleural mesothelioma and asbestos-exposed subjects. (24th April 2018) - Pesatori, AC; Angelici, L; Favero, C; Dioni, L; Mensi, C; Bareggi, C; Palleschi, A; Cantone, L; Consonni, D; Bordini, L; Todaro, A; Bollati, V
Abstract : Introduction: Malignant Pleural Mesothelioma (MPM) is an aggressive cancer mainly caused by asbestos exposure. Due to its long latency and insidious onset, MPM is often diagnosed in advanced stages with poor prognosis. In addition, asbestos is still used in many non-European countries and the incidence of MPM is expected to increase. In this context, the need of reliable diagnostic markers for early MPM diagnosis is of paramount importance. Along with the more frequently studied biological markers (mesothelin, fibulin-3), new emerging biomarkers include miRNA expression in peripheral blood. Methods: We previously investigated 23 MPM patients and 19 subjects with past asbestos exposure (PAE) to examine if a specific miRNA signature in plasmatic extracellular vesicles (EV) might help to discriminate between MPM and PAE ( PLoS One, 2017 ). Criteria for enrollment, blood collection, miRNA extraction, screening and validation have been previously described. We found a two miRNA (miR-103a-3p and mir-30-3ep) diagnostic signature that discriminates the two groups with high accuracy (AUC 0.942), high sensitivity (95.5%) and good specificity (80.0%). We are currently expanding our study population to additionally include 25 MPM cases, 50 subjects with PAE, and 20 subjects with other respiratory diseases. Alongside miRNA expression, plasma mesothelin and fibulin-3 will be also measured. Results: The diagnostic performance (AUC, Sensitivity and Specificity) of the best five miRNAs previously detected in our study will be examined in combination with plasma mesothelin and fibulin-3, taking into account major confounders (e.g. age, gender, BMI and smoking habit). Conclusions: The combination of biological markers belonging to different molecular pathways might help in identifying a panel of biomarkers able to improve the overall diagnostic performance as suggested by Weber et al. ( PLoS One, 2014 ), who recently showed an improved AUC of 0.93 when combining mesothelin and miR-103a-3p.